Isolation and identification of mycobacteria from livestock specimens and milk obtained in Brazil - Leite, Clarice Q Fujimura; Anno, Ivone S; Leite, Sergio R de Andrade [UNESP]; Roxo, Eliana; Morlock, Glenn P; Cooksey, Robert C (Instituto Oswaldo Cruz, Ministério da Saúde, 2003)
The prevalence of Mycobacterium bovis and other mycobacterial species in livestock specimens and milk was evaluated. An emphasis was placed upon the distribution of these organisms in milk that is readily available to the public that was either untreated, pasteurized, or treated using ultra high temperature. Twenty-two pathologic specimens from livestock (bovine, swine and bubaline) in five Brazilian states and 128 bovine milk samples from retail markets in the State of São Paulo were examined for mycobacteria. Identification was made by classical biochemical tests, thin layer chromatography of mycolic acids and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis. Mycobacteria were isolated from 15 (68.2%) caseous lesions and from 23 (18%) milk samples. Eleven isolates were identified as M. bovis, and the remaining 27 nontuberculous mycobacterial isolates were represented by five species and six unidentified rapidly growing mycobacterial strains. The data demonstrate that animal products in Brazil are frequent reservoirs of mycobacteria and may pose a risk to the public.
Keywords: Mycobacterium; livestock; bovine; polymerase chain reaction (PCR); restriction fragment length polymorphism (RFLP); mycolic acid analysis; Brazil